2007
DOI: 10.1089/ten.2006.0209
|View full text |Cite
|
Sign up to set email alerts
|

Heterobifunctional Poly(Ethylene Glycol)–Tethered Bone Morphogenetic Protein-2–Stimulated Bone Marrow Mesenchymal Stromal Cell Differentiation and Osteogenesis

Abstract: We describe a biomimetic mode of insoluble signaling stimulation to provide target delivery of bone morphogenetic protein-2 (BMP-2), with the aim of prolonging the retention of BMP-2 use in bone tissue engineering and to enable its localized release in response to cellular activity. In our novel localization process, we used heterobifunctional acrylate-N-hydroxysuccinimide poly(ethylene glycol) (PEG) as a spacer to tether BMP-2 onto a poly(lactide-co-glycolide) scaffold. Use of PEG-tethered BMP-2 was feasible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 37 publications
0
69
0
Order By: Relevance
“…Interestingly, previous studies and our current study have shown the distinctive release pattern of the conjugated BMPs from the biomaterial surface with different conjugation strategies and biomaterials. [13][14][15] The different release patterns in different studies may indicate that the conjugation strategy as well as the material itself also affect the release pattern.…”
Section: Bmp-2 Conjugation On Pcl Scaffolds Elicits Bioactivitymentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, previous studies and our current study have shown the distinctive release pattern of the conjugated BMPs from the biomaterial surface with different conjugation strategies and biomaterials. [13][14][15] The different release patterns in different studies may indicate that the conjugation strategy as well as the material itself also affect the release pattern.…”
Section: Bmp-2 Conjugation On Pcl Scaffolds Elicits Bioactivitymentioning
confidence: 99%
“…The possibility of substrate bound growth factors influencing cell behavior has been confirmed by several studies. Studies conjugating BMPs on biomaterials such as PLGA, 12,14,15 titanium, 25 and chitosan 16 have demonstrated that the conjugated BMPs maintain their bioactivity, stimulating increased cell proliferation and differentiation. More importantly, in vivo studies using conjugated BMP-2 on PLGA scaffolds induced bone formation in a rabbit femoral defect 12 and in a hind limb defect.…”
Section: Bmp-2 Conjugation On Pcl Scaffolds Elicits Bioactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Growth factors, including TGF-b1, have been covalently immobilized or tethered onto other polymer scaffolds or hydrogels with other cell types [2,8,20,21,29,34], sometimes with altered signaling as a result [10,35,42]. The density of tethered growth factors can also affect bioactivity [45]; however, both IGF-1 and TGF-b receptors exist as functional complexes on cell surfaces, and binding of one ligand can initiate signaling [9,43].…”
Section: Discussionmentioning
confidence: 99%